2020
DOI: 10.1038/s41438-020-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Gynoecy instability in cucumber (Cucumis sativus L.) is due to unequal crossover at the copy number variation-dependent Femaleness (F) locus

Abstract: Cucumber, Cucumis sativus is an important vegetable crop, and gynoecy has played a critical role in yield increase of hybrid cucumber production. Cucumber has a unique genetic system for gynoecious sex expression, which is determined by the copy number variation (CNV)-based, dominant, and dosage-dependent femaleness (F) locus. However, this gynoecy expression system seems unstable since monecious plants could often be found in Fdependent gynoecious cucumber inbreds. We hypothesized that gynoecy instability (gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 82 publications
(120 reference statements)
0
12
0
Order By: Relevance
“…Seeds of 9930 and WI7602 were kindly supplied by Xingfang Gu (Chinese Academy of Agricultural Sciences, Beijing, China) and Sen Li (Shanxi Agricultural University, China), respectively. Gy14M (also known as Gy14M42) is the monoecious version of the gynoecious Gy14 [ 41 ]. H19 is a littleleaf ( LL ) mutant [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seeds of 9930 and WI7602 were kindly supplied by Xingfang Gu (Chinese Academy of Agricultural Sciences, Beijing, China) and Sen Li (Shanxi Agricultural University, China), respectively. Gy14M (also known as Gy14M42) is the monoecious version of the gynoecious Gy14 [ 41 ]. H19 is a littleleaf ( LL ) mutant [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…ACS encodes a 1-aminocyclopropane-1-carboxylic acid (ACC) synthase catalysing the conversion of S-adenosylmethionine (SAM) to form ACC, and ethylene is then synthesized from ACC, which is catalysed by ACC oxidase encoded by ACO (Boualem et al, 2015). For example, a unique F locus associated with gynoecy was identi ed in cucumber, and previous works have suggested that monoecious plants carry only one CsACS1 gene, while gynoecious plants have not only the CsACS1 gene but also an additional copy of CsACS1 named CsACS1G (F) (Mibus & Tatlioglu, 2004;Li et al, 2020). The loss of function of the androecy (a) gene CsACS11/CmACS11, which is the hypostatic gene of F and controls female ower development, leads to androecious cucumber and melon plants (Boualem et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…QTL-seq combines the next-generation sequencing technology with BSA for rapid detection of QTLs for any particular trait and facilitate development of closely associated molecular markers and identification of candidate genes. Thereafter, QTL-seq has been widely used for the detection of QTLs, identification of closely linked molecular markers and identification of candidate genes for number of traits in different crops ( Singh et al., 2016 ; Wang et al., 2016 ; Wei et al., 2016 ; Chen et al., 2017 ; Wen et al., 2019 ; Arikit et al., 2019 ; Li et al., 2020 ). In cucumber, QTL-seq has been used successfully for the identification of QTL for early flowering traits ( Lu et al., 2014 ), flesh thickness ( Xu et al., 2015 ), sub-gynoecy sex expression ( Win et al., 2019 ), pre-harvest sprouting of the seeds ( Cao et al., 2021 ) and resistance to powdery mildew ( Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%